2009
DOI: 10.1111/j.1745-7599.2009.00406.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of nurse practitioner cultural competence on Latina patient satisfaction

Abstract: The provision of culturally competent care leads to negotiation, mutual exchange of information, increased compliance, and improved patient-provider communication. Similarly, patient satisfaction with care is associated with increased compliance and greater continuity of care. Employers seeking to meet the healthcare demands of a growing Latino population must look at extrinsic values such as NPs' certification, cultural competence training, education, and ability to speak Spanish.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(61 citation statements)
references
References 34 publications
(42 reference statements)
4
46
0
4
Order By: Relevance
“…Castro and Ruiz (2009) in their study comparing nurse practitioner levels of cultural competence with Latina patient satisfaction scores found that longer wait times were associated with lower satisfaction scores. A primary reason cited by the authors was that the patients often have to bring their children with them to an environment not conducive to the energy and exuberance of children (Castro & Ruiz, 2009 Keller (2008) found in studying Mexican parents' perceptions regarding their relationships with rural clinic nurses that the race and ethnicity of the practitioner is not as important as their ability to speak in the patient's language.…”
Section: Physical Environmentmentioning
confidence: 99%
See 4 more Smart Citations
“…Castro and Ruiz (2009) in their study comparing nurse practitioner levels of cultural competence with Latina patient satisfaction scores found that longer wait times were associated with lower satisfaction scores. A primary reason cited by the authors was that the patients often have to bring their children with them to an environment not conducive to the energy and exuberance of children (Castro & Ruiz, 2009 Keller (2008) found in studying Mexican parents' perceptions regarding their relationships with rural clinic nurses that the race and ethnicity of the practitioner is not as important as their ability to speak in the patient's language.…”
Section: Physical Environmentmentioning
confidence: 99%
“…Having to wait up to 12 hours or more for an appointment has been shown to be a barrier to accessing care in this population (Cristancho, Garces, Peters, & Mueller, 2008;Derose, 2000;Nailon, 2004;Sorkin, Ngo-Metzger, & DeAlba, 2010) as the expectation is often for timely care with treatments that provide rapid results (Clark & Redman, 2007). Castro and Ruiz (2009) in their study comparing nurse practitioner levels of cultural competence with Latina patient satisfaction scores found that longer wait times were associated with lower satisfaction scores. A primary reason cited by the authors was that the patients often have to bring their children with them to an environment not conducive to the energy and exuberance of children (Castro & Ruiz, 2009 Keller (2008) found in studying Mexican parents' perceptions regarding their relationships with rural clinic nurses that the race and ethnicity of the practitioner is not as important as their ability to speak in the patient's language.…”
Section: Physical Environmentmentioning
confidence: 99%
See 3 more Smart Citations